Pre-travel consultations quality criteria: a Delphi consensus - Wakimoto, Mayumi Duarte (2021)
With the exponential growth of international travel over the last decades, the question of travellers’ health has taken on a crucial importance. International tourism, occupational travel and migratory fluxes have all contributed to this phenomenon which has drawn the attention of international organizations and national authorities on the risks associated with the spread of infectious diseases. The increasing concerns over emerging and re-emerging diseases has raised the global profile of travel medicine, urging the setting of quality standards in clinical practice and service delivery to travellers. The present study aimed to obtain a broad consensus on quality assessment criteria for pre-travel advice among practitioners in Portugal and Brazil based upon the Delphi method, using international criteria and standards and scientific studies as benchmarks. Our proposed model which integrates the consensual criteria obtained in our study, identified differences in quality criteria between the two expert groups. Nevertheless, they did highlight the importance attributed to qualified human resources, the quality of information for travelers and health professionals, and timely diagnosis, amongst others. The cases of Portugal and Brazil discussed here, underscore the need for more studies on the quality of pre- and post-travel consultations at national and transnational level.